1998
DOI: 10.1590/s0103-90161998000200014
|View full text |Cite
|
Sign up to set email alerts
|

ALTURA DE VÔO DAS ABELHAS AFRICANIZADAS (Apis mellifera L.) PARA COLETA DE ALIMENTOS

Abstract: O presente trabalho foi realizado com o objetivo de verificar até que altura as abelhas africanizadas deslocam-se para a coleta de alimentos e se existe preferência destas abelhas por alguma altura. Instalou-se, num eucalipto de mais de 30m, um sistema de roldana que possibilitava a colocação de armadilhas a diferentes alturas, para a captura dos insetos que ali fossem se alimentar. As médias do número de abelhas coletadas em sete alturas (de 0 a 30m) decresceram com o aumento da altura e o melhor ajuste foi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…Evidência de que essas abelhas preferem forragear em estratos mais baixos foi encontrada por Moretti & Marchini (1998). Segundo esses autores, o número de abelhas africanizadas que visitou as iscas de mel+água colocadas a 0, 5, 10, 15, 20, 25, 30m do solo, em um eucaliptal no estado São Paulo, decresceu linearmente com a altura.…”
Section: Resultsunclassified
“…Evidência de que essas abelhas preferem forragear em estratos mais baixos foi encontrada por Moretti & Marchini (1998). Segundo esses autores, o número de abelhas africanizadas que visitou as iscas de mel+água colocadas a 0, 5, 10, 15, 20, 25, 30m do solo, em um eucaliptal no estado São Paulo, decresceu linearmente com a altura.…”
Section: Resultsunclassified
“…These pollens were a constant presence in the collections of A. mellifera and were present in a few collections of M. obscurior, similar to other studies of Melipona quadrifasciata anthidioides Lepeletier (Antonini et al 2006) and Melipona scutellaris Latreille (Ramalho et al 2007). However, A. mellifera displays some preference for foraging on herbs (Moretti and Marchini 1998), which include the majority species of Poaceae and Asteraceae (Boff et al 2011). Conversely, Solanaceae species, particularly S. mauritianum, were heavily exploited by M. obscurior in Riozinho and were present in a few A. mellifera collections as occasional pollen.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those observed by Diniz et al 8 and Linard et al 9 . Moreti and Marchini 12 have evaluated the flight altitude of the Africanized honey bee hives and concluded that the maximum flight altitude reached was 1.62 meters. This corresponds approximately to the height of the head or upper limbs of the average Brazilian population.…”
Section: /6mentioning
confidence: 99%